Stress, coping and emotions among Malaysian elite tenpin bowlers: a mixed methods approach - Wong, Sook Kwan (N/A, 2015)
Stress, coping and emotions among Malaysian elite tenpin bowlers: a mixed methods approach by Wong, Sook Kwan